Is Putin's popularity real?. Issue 1 (2nd January 2017) - Frye, Timothy; Gehlbach, Scott; Marquardt, Kyle L.; Reuter, Ora John
Abstract: Vladimir Putin has managed to achieve strikingly high public approval ratings throughout his time as president and prime minister of Russia. But is his popularity real, or are respondents lying to pollsters? We conducted a series of list experiments in early 2015 to estimate support for Putin while allowing respondents to maintain ambiguity about whether they personally do so. Our estimates suggest support for Putin of approximately 80%, which is within 10 percentage points of that implied by direct questioning. We find little evidence that these estimates are positively biased due to the presence of floor effects. In contrast, our analysis of placebo experiments suggests that there may be a small negative bias due to artificial deflation. We conclude that Putin's approval ratings largely reflect the attitudes of Russian citizens.